A study on RDP loans and the investment costs of some IGAs - Matin, Rukhsana; Rab, Habib N. (BRAC, 2019)
This paper is a cost study of the six most commonly performed micro-enterprises in four village organizations. It is an investigation to see whether loans for these micro enterprises restrict borrower's ability to meet the purchase cost of working capital and thus sustain themselves. Fixed and variable costs were estimated to calculate total investment cost. Project viability was assessed by calculating the return on investment in terms of the return on investment. Out of a total sample of 114 respondents, the key findings show that for IGAs with no gestation gaps, namely trading and paddy husking, loans were on the whole sufficient to cover investment cost. However, investment costs in these cases are also a function of factors such as the scale of operation and prior involvement with the activity. For IGAs with gestation gaps, namely vegetable cultivation, milch cow and chick rearing, it is recommended that loan sizes may be increased due to large initial investment outlays.